Mother's Knowledge on HIV, Syphilis, Rubella, and Associated Factors in Northern Tanzania: Implications for MTCT Elimination Strategies. (9th July 2020) - Chotta, Nikolas A. S.; Msuya, Sia E.; Mgongo, Melina; Hashim, Tamara H.; Stray-Pedersen, Arne
Abstract : Background . Infections transmitted from mother to child (MTCT) during pregnancy, childbirth, and breastfeeding contribute significantly to the high infant and childhood morbidity and mortality in sub-Saharan African countries. The most significant and preventable of these include HIV, syphilis, and rubella. To achieve elimination, mothers need to be aware of and to understand effective preventive measures against these infections. Lack of comprehensive knowledge on transmission and prevention of MTCT infections is one of the factors hindering achievement of the elimination goals for these infections. The aim of this study was to assess the knowledge of HIV, syphilis, rubella, and associated factors among mothers in the Kilimanjaro region of Tanzania. Methods . We conducted a community-based cross-sectional study in three districts of the Kilimanjaro region from September to October 2016. The study involved mothers with children up to five years of age. Data collection involved the use of a questionnaire, administered by face-to-face interviews. Logistic regression analysis was used to assess predictors of mothers' knowledge on MTCT infections. Results . A total of 618 mothers were recruited, with a mean age of 29.6 (SD 7.6) years. The overall knowledge on MTCT infections was low. The highest level of knowledge on MTCT infections was regarding HIV (89.2%). Fewer mothers had knowledge of syphilis (27.8%). Rubella was the least known; only 12% of mothers were aware of rubella infection. District of residence and having knowledge of syphilis were predictors for rubella knowledge, while for syphilis knowledge, significant predictors were age group, occupation, and those having knowledge on HIV and rubella. Predictors for HIV knowledge were residential district, having a mobile phone, and those having knowledge of syphilis and rubella. Conclusions . This study confirmed that mothers have low overall knowledge on MTCT infections. To achieve the MTCT elimination goals, targeted interventions to improve knowledge among women of childbearing age are recommended.